1997
DOI: 10.1021/es960793i
|View full text |Cite
|
Sign up to set email alerts
|

Crude Oil Hydrocarbon Bioremediation and Soil Ecotoxicity Assessment

Abstract: In this study, we determined the limits and extent of hydrocarbon biodegradation, earthworm and plant toxicity, and waste leachability of crude oil-containing soils. Three oils (heavy, medium, and light of API gravity 14, 30, and 55, respectively) were mixed into silty loamy soils containing low (0.3%) or high (4.7%) organic carbon at 4000−27 000 mg/kg TPH. Hydrocarbon bioremediation in these artificially weathered oily soils usually followed first-order removal rates in which 50−75% and 10−90% of the total pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
138
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(168 citation statements)
references
References 34 publications
19
138
0
6
Order By: Relevance
“…Lowered hydrocarbon bioavailability is attributed to increased hydrocarbon sequestration onto organic matter and therefore, decreased bioavailability, which is consistent with equilibrium partitioning for neutral organics based on sorption coefficients [29][30][31][32].…”
Section: Discussionsupporting
confidence: 71%
“…Lowered hydrocarbon bioavailability is attributed to increased hydrocarbon sequestration onto organic matter and therefore, decreased bioavailability, which is consistent with equilibrium partitioning for neutral organics based on sorption coefficients [29][30][31][32].…”
Section: Discussionsupporting
confidence: 71%
“…The lack of synchrony by different groups of organisms in response to the loss of hydrocarbons that we saw has been observed in other studies (Hund and Traunspurger, 1994;Salanitro et al, 1997;Sayles et al, 1999). In general, the inhibition of plant growth persisted longer than the effects on invertebrate viability or toxicity measured by Microtoxâ (Salanitro et al, 1997;Hund and Traunspurger, 1994).…”
Section: Lack Of Synchrony Of Recoverysupporting
confidence: 81%
“…In general, the inhibition of plant growth persisted longer than the effects on invertebrate viability or toxicity measured by Microtoxâ (Salanitro et al, 1997;Hund and Traunspurger, 1994). Hund and Traunspurger (1994) also found that nematodes and nitrification were very sensitive to petroleum contamination: nematodes were not found in heavily contaminated soils and were still at much reduced densities after 4 months, ammonium oxidation showed partial recovery after 7 months, and nitrite oxidation after 10 months of bioremediation.…”
Section: Lack Of Synchrony Of Recoverymentioning
confidence: 97%
See 1 more Smart Citation
“…There are no universal TPH cleanup standards for soils contaminated with crude oils [23]. Some guidelines have been developed for oil content.…”
Section: Discussionmentioning
confidence: 99%